1998
DOI: 10.1001/archpedi.152.6.531
|View full text |Cite
|
Sign up to set email alerts
|

Violence Exposure and Emotional Trauma as Contributors to Adolescents' Violent Behaviors

Abstract: To investigate the degree to which violence exposure and symptoms of psychological trauma are related to adolescents' own violent behaviors.Design and Setting: Anonymous self-report questionnaire administered to students in 6 public high schools (grades 9-12).Participants: Sixty-eight percent of the students attending the participating schools during the survey participated in the study (N=3735). Ages ranged from 14 to 19 years; 52% were female; and 35% were African American, 33% white, and 23% Hispanic. Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
74
2
3

Year Published

1998
1998
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 130 publications
(80 citation statements)
references
References 35 publications
1
74
2
3
Order By: Relevance
“…Several studies suggest that long-term exposure to community violence may have a profound negative impact on children's cognitive, social, psychological, and moral development (Fry-Bowers, 1997;Perry & Azad, 1999). In addition, community violence exposure has been associated with aggressive behaviors in adolescents (Song, Singer, & Anglin, 1998). Although this study was designed to characterize violence exposure among pregnant drug-dependent women, the potential effects of exposure to violence among their children should not be underestimated.…”
Section: Discussionmentioning
confidence: 98%
“…Several studies suggest that long-term exposure to community violence may have a profound negative impact on children's cognitive, social, psychological, and moral development (Fry-Bowers, 1997;Perry & Azad, 1999). In addition, community violence exposure has been associated with aggressive behaviors in adolescents (Song, Singer, & Anglin, 1998). Although this study was designed to characterize violence exposure among pregnant drug-dependent women, the potential effects of exposure to violence among their children should not be underestimated.…”
Section: Discussionmentioning
confidence: 98%
“…Some studies have found that maltreatment increases the risk of delinquency among females but not among males [46][47][48]. Females are also more likely to exhibit aggressive behaviors as they get older [49,50]. At the same time, females are more likely to anticipate disapproval of delinquency from parents or peers than males [51].…”
Section: The Role Of Gender and Place On Parental Maltreatmentmentioning
confidence: 99%
“…A study conducted by Singer et al (83) with 2000 elementary school-aged children showed that exposure to violence in the past year was the most significant contributor to predicting violent behavior, even after controlling for demographics, parental monitoring, and television viewing habits. Song and associates (88) found that violence exposure and symptoms of psychological trauma together explained more than 50% of the variance in male and female self-reported violent behavior. In addition to community violence, children who are abused or exposed to family violence display more aggressive and violent behavior (27).…”
Section: Why Youth Become Violent: Developmental Pathways To Youth VImentioning
confidence: 99%